Internet addiction and depressive symptoms in adolescents: joint trajectories and predictors - Zhang, Junjie; Wang, Enna; Zhang, Long; Chi, Xinli (Frontiers in Public Health, 2024)
Objective: Internet addiction and depressive symptoms are common mental health problems in adolescents. Due to the comorbidity of Internet addiction and depressive symptoms, their mutual relationship influences their developmental trajectories over time. Thus, this study aimed to identify the joint trajectories of Internet addiction and depressive symptoms, and examined the individual, family, and school antecedents of these trajectories among Chinese adolescents.Methods: Using a battery of self-report scales, three waves of data collection were conducted in a Chinese adolescent sample (N = 1301). The co-developmental trajectories of Internet addiction and depressive symptoms were extracted by adopting parallel-process latent class growth modeling (PPLCGM). Multinomial logistic regression was performed to assess predictive factors.Results: Four unique joint trajectory classes were detected: the Health Group (n=912, 70.1%), Comorbidity-Worsening Group (n=85, 6.5%), Asymptomatic-Comorbid Risk Group (n=148, 11.4%), and Prominent Depressive Symptoms-Remission Group (n=156, 12.0%). Individual, family, and school factors (e.g., gender, positive youth development, family function, academic performance) significantly predicted the membership in these distinct co-developmental trajectories. Conclusion: Our findings illustrate that the joint development of Internet addiction and depressive symptoms among adolescents presents a heterogeneous distribution, which could better inform prevention and intervention strategies since each co-developmental trajectory may represent unique experience for adolescents who need targeted treatment. Various individual, family, and school factors are important predictors that play different roles in distinguishing the joint trajectories of Internet addiction and depressive symptoms during this critical developmental transition period.